Nanoscale frontiers in cancer diagnosis and therapy - Tamer A. Addissouky (Discover Chemistry)
Abstract Background Cancer nanomedicine leverages the unique properties of nanoscale materials to transform cancer diagnosis, treatment, and monitoring. Although significant progress has been made, the clinical translation of these technologies faces persistent scientific, technical, and regulatory challenges. Purpose This review critically examines the landscape of cancer nanomedicine, focusing on recent breakthroughs, comparative analyses of nanoparticle technologies, and the integration of emerging fields such as artificial intelligence and biomimetic engineering. The goal is to provide a nuanced, mechanism-driven synthesis that highlights both transformative potential and current limitations. Main body The article systematically analyzes key nanomaterial platforms—quantum dots, upconversion and plasmonic nanoparticles, liposomes, polymeric and inorganic carriers—and their roles in diagnostics, targeted therapy, liquid biopsies, and cancer immunotherapy. Comparative evaluations elucidate the physicochemical properties, biocompatibility, and translational challenges associated with each platform. The manuscript identifies critical bottlenecks, such as nanoparticle heterogeneity, immunogenicity, and large-scale manufacturing, and discusses regulatory and clinical trial considerations vital for successful adoption. Furthermore, it explores the future convergence of nanotechnology with artificial intelligence, machine learning, and advanced imaging, emphasizing the potential for personalized and precision medicine. The review also addresses emerging ethical and technical challenges, including data privacy and algorithmic transparency, as nanomedicine moves toward clinical reality. Conclusion Cancer nanomedicine is evolving toward more sophisticated, adaptive, and patient-specific solutions. Overcoming translational and regulatory hurdles—through multidisciplinary collaboration, innovative clinical trial design, and the integration of AI—will be pivotal in realizing the full clinical impact of nanotechnology-enabled cancer care. Graphical Abstract